A Study of Investors’ Preference towards Mutual Funds in Kathmandu Metropolitan City, Nepal - Bajracharya, Rajan Bilas; Mathema, Rushil Bhakta (Journal of Advanced Academic Research, 2018)
A Mutual Fund is an investment vehicle that pools funds from various investors and invests the funds in stocks, bonds, short-term money-market instruments, other securities or assets or some combination of these investments. The primary goal behind investment in mutual fund is to earn goods return with comparatively low risk. The main objective of this research is to identify investors’ preference towards mutual fund in Kathmandu metropolitan city. By using in structured questionnaire, Description statistical tools like chi-square test have been used for analyzing the data. The findings from this research are that the most of the investors are doubtful to invest the new age investment like mutual funds.